2014
DOI: 10.1080/13691058.2014.894206
|View full text |Cite
|
Sign up to set email alerts
|

Basic deprivation and involvement in risky sexual behaviour among out-of-school young people in a Lagos slum

Abstract: Research has shown that in countries such as Nigeria many urban dwellers live in a state of squalour and lack the basic necessities of food, clothing and shelter. The present study set out to examine the association between forms of basic deprivation--such as food deprivation, high occupancy ratio as a form of shelter deprivation, and inadequate clothing--and two sexual outcomes--timing of onset of penetrative sex and involvement in multiple sexual partnerships. The study used survey data from a sample of 480 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…For example, in Uganda, Kenya, and Lesotho, studies have shown that young women increased supply of sex to acquire luxury goods, such as mobile phones and high-priced clothing [10, 29], but had greater choice whether to use a condom or engage in sex or not when earning salary through employment [76]. In Nigeria, a study also found that attempts to mitigate food deprivation partly explained slum adolescent girls’ engaging in risky sexual behaviors [77]. The observation that men have more non-sexual opportunities to earn income has been documented in Mozambique and Haiti [28, 78], and was also described among our youth in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Uganda, Kenya, and Lesotho, studies have shown that young women increased supply of sex to acquire luxury goods, such as mobile phones and high-priced clothing [10, 29], but had greater choice whether to use a condom or engage in sex or not when earning salary through employment [76]. In Nigeria, a study also found that attempts to mitigate food deprivation partly explained slum adolescent girls’ engaging in risky sexual behaviors [77]. The observation that men have more non-sexual opportunities to earn income has been documented in Mozambique and Haiti [28, 78], and was also described among our youth in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kenyan young adults within the lowest wealth quintile and in urban areas have higher HIV prevalence (3.1% and 7.2%) in comparison to wealthier young adults (2.6%) living in rural areas (6.0%) [5]. Young adults living in urban slum settlements engage frequently in sexual risk behaviors, such as condomless sex, transactional sex, or sex with multiple concurrent sexual partners that result in higher risk of HIV and other sexually transmitted infections [6][7][8][9]. In addition to being at increased risk for HIV, young adults living in urban slum settlements are often hidden and not well reached using traditional surveillance systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Deprivations of material resources such as food, housing and health care are currently receiving increased research attention as critical in uences of sexual risk in disadvantaged urban settings in sub-Saharan Africa [10][11][12][13]. This attention is premised on the understanding that traditional income-related measures of disadvantage (income, wealth and education) do not re ect unique basic needs, particularly for vulnerable groups of young people living in urban disadvantaged settings [3,13,14]. In this regard, urban scholars have suggested a shift from income-related measures of disadvantage to measures that capture critical aspects of disadvantage that best represent the unique needs of vulnerable groups in poor urban settings [10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…This attention is premised on the understanding that traditional income-related measures of disadvantage (income, wealth and education) do not re ect unique basic needs, particularly for vulnerable groups of young people living in urban disadvantaged settings [3,13,14]. In this regard, urban scholars have suggested a shift from income-related measures of disadvantage to measures that capture critical aspects of disadvantage that best represent the unique needs of vulnerable groups in poor urban settings [10,13,15]. These measures include aspects of housing quality, instability and overcrowding [16]; availability, accessibility and utilization of food [17] and affordability, acceptability and availability of health care [18,19].…”
Section: Introductionmentioning
confidence: 99%